Emotions, Bayesian inference, and financial decision making - Diego Salzman; Emanuela Trifan (Technische Universität Darmstadt, Department of Law and Economics, 2005)
This paper presents a model in which rational and emotional investors are compelled to make decisions under uncertainty in order to ensure their survival. Using a neurofinancial setting, we show that, when different investor types fight for market capital, emotional traders tend not only to influence prices but also to have a much more developed adaptive mechanism than their rational peers, in spite of their apparently simplistic demand strategy and distorted revision of beliefs. Our results imply that prices in financial markets could be seen more accurately as a thermometer of the market mood and emotions rather than as simple informative signals as stated in traditional financial theory.
Keywords: G1; 330; Judgement under uncertainty; Bayesian Inference; Behavioral Finance; Decision Making; Emotions